EFFECT OF SOYBEAN SEEDS AND URANYL NITRATE ON APOPTOSIS IN SPLEEN IN MALE RATS - Al-Hilfy, Jabber; Al-Kaisy, Kawkab (Iraqi Journal of Science, 2024)
The effects of Soybean and Uranyl nitrate on the percentage, ultra structure and morphology of apoptosis in the spleen were investigated. Prepubertal albino male rats were equally divided as follows :control G1, G2 was given intragastrically 75mg / kg / b.w Uranyl nitrate, G3 was fed a diet contains 20% Soybean, and G4 was treated with both Uranyl nitrate and Soybean as in G2 and G3.The results showed a significant increase (p<0.05) in the mean value of percentage of apoptotic cells in the spleen in G2, G3 and G4 in comparison with control group and significant decrease (p<0.05) was observed in (G4) in comparison with (G2).In the study of electron microscope there was an increase in the number of spleenocytes that were in the early and later phases of apoptosis in the (G2) group which were characterized by chromatin condensation and chromatin aggregation in a crescent shape near the nuclear envelope, in addition to that some of these cells were characterized by chromatin fragmentation, irregular nuclear envelope and disappearance of chromatin.In the (G3) most of spleenocytes were in the normal appearance and some in the early and later phase of apoptosis. While in the (G4) there were numbers of spleenocytes in the normal appearance and others in different phases of apoptosis. From these results we can conclude that the treatment with Uranyl nitrate has a negative effect, and the active components of soybean reflect an important role in the inhibition of these effects on apoptosis in spleen.